Further evidence for bow hunting and its implications more than 60 000 years ago: Results of a use-trace analysis of the bone point from Klasies River Main site, South Africa. (15th May 2020) - Bradfield, Justin; Lombard, Marlize; Reynard, Jerome; Wurz, Sarah
Abstract: The bone point (SAM 42160) from >60 ka deposits at Klasies River Main Site, South Africa, is reassessed. We clarify the stratigraphic integrity of SAM 42160 and confirm its Middle Stone Age provenience. We find evidence that indicates the point was hafted and partially coated in an adhesive substance. Internal fractures are consistent with stresses occasioned by high-velocity, longitudinal impact. SAM 42160, like its roughly contemporaneous counterpart, farther north at Sibudu Cave, likely functioned as a hafted arrowhead. We highlight a growing body of evidence for bow hunting at this early period and explore bow-and-arrow technology might imply about the cognition of people in the Middle Stone Age who were able to conceive, construct and use it. Highlights: The bone point (SAM 42160) from >60 ka deposits at Klasies River Main Site, South Africa, is reassessed. We clarify the stratigraphic integrity of SAM 42160 and confirm its Middle Stone Age provenience. Evidence indicate the point was hafted, experienced high-velocity, longitudinal impact, and was partially coated in an adhesive substance. SAM 42160 likely functioned as a hafted arrowhead. E explore the cognitive implications for bow hunting in the Middle Stone Age.